Reviews of Physiology, Biochemistry and Pharmacology Volume 162 - Nilius, Bernd; Amara, Susan G.; Gudermann, Thomas; Jahn, Reinhard; Lill, Roland; Offermanns, Stefan; Petersen, Ole H. (Reviews of Physiology, Biochemistry and Pharmacology, 2012)
M. Grunnet, B.H. Bentzen, U.S. Sorensen, J.G. Diness: Cardiac Ion Channels and Mechanisms for Protection Against Atrial Fibrillation. G.E. Pickard and P.J. Sollars: Intrinsically Photosensitive Retinal Ganglion Cells. T. Voets: Quantifying and Modeling the Temperature-dependent Gating of TRP Channels.  .